A Discussion on the relationship between prominent unconformities on the SCS shelf margins and the end of seafloor spreading in the South China Sea - Kessler, Franz; Jong, John (Ikatan Ahli Geologi Indonesia, 2023)
In an effort to reconcile different data sources (seafloor spreading, seismic and gravity images, well calibrations, outcrop studies) in the South China Sea (SCS), we reviewed the unconformity records, in particular in the context with the shut-off of seafloor spreading in the SCS. With respect to the start of spreading, there is a consensus: ca. 34-41 Ma. Recent data infer an end of spreading, near to the magnetic Anomaly 5 = ca. 15.5 Ma (Langhian age). In Northwest Borneo, it is suggested that this event is coeval with the Deep Regional Unconformity (DRU) in Sabah and Brunei, and the Mid-Miocene Unconformity (MMU) in Sarawak. The MMU is also recognized in offshore Vietnam and Palawan, on the Western and Southeastern margins of the SCS, respectively. The MMU/DRU may constitute the border between active margin and passive margin deposits within the marine SCS sub-basins. The progradation of clastic shelves post-MMU/DRU may have hampered growth of bioherms whilst creating prolific sandstone reservoir sequences offshore Northwest Borneo and Vietnam.